Production of Bioethanol from Kundur [Benincisa Hispida (Thunb) Cogn] - Siti Salbiah, Mutalib (2013)
Bioethanol is a clean burning, renewable resources which has become one of the alternative biofuels which are environmentally friend. Bioethanol has been proved that it can be produced by using agro-industrial and food wastes. Kundur (Benincasa hispida) also known as fuzzy melon is a vegetable crop that popular in Asian for their nutritional and medical attributes such as anti-obesity, anti-inflammatory, anti-diarrheal, antioxidant and etc. The aim of the study is to investigate the production of bioethanol from Kundur. This study was conducted by using different parts of Kundur. The moisture contents in Kundur seeds, pulps and fleshes are 77, 86 and 97 % (w/w) respectively. Kundur fleshes have the highest amount of reducing sugar (glucose) and carbohydrate contents which is 2.909 and 79.885 g/L. Meanwhile the amount of reducing sugar and carbohydrate are 0.924 and 33.333 g/L for Kundur seeds and 0.796 and 13.103 g/L for Kundur pulps. Kundur juices were selected for the batch fermentation in the shake flasks to investigate the suitability of Kundur juice to produce ethanol by using Saccharomyces Cerevisae as yeast. The fermentation process was carried out in duplicate at 30°C, pH 5.5 and 200rpm for 72hours. According to the results obtained, the ethanol yield for the fermentation process without nutrient supplement is in the range of -0.192~ -0.194 (g ethanol/g biomass) while the specific growth rate is in the range of -0.0148~ -0.015h-1. As for the fermentation process with nutrient supplement, the ethanol yield and specific growth rate is in the range of -0.136~ -0.1442 (g ethanol/g biomass) and -0.017h-1. Hence, we can conclude that Kundur juice is not suitable for ethanol production.